RICERCHE TERRITORIALI E RISORSE GEOMATICHE APPLICATE ALL'INDAGINE ARCHEOLOGICA NELL'OASI DI FARAFRA - BARICH, BARBARA E.; CRESPI, MATTIA G.; FABIANI, ULISSE; LUCARINI, GIULIO (Archeomatica, 2012)
Italian Archaeological Mission in the Farafra Oasis – Egypt - The archaeologicalresearch in desert areas has long employed multidisciplinary fi eld and laboratorymethods. The Italian Archaeological Mission in the Farafra Oasis – Egyptof the Sapienza University of Rome benefi ts from three decades of experienceduring which it has kept pace with the latest developments in fi eldwork techniques.Geomatic techniques, as used by the Geodesy and Geomatic Area ofthe same university, are particularly important for archaeological research concernedwith large geographical areas. The paper shows how survey was organisedthrough several stages, from the creation of accurate maps, to photoplansof signifi cant structures and to DEMs of the different fi nd locations. Processingthe cartographic data from the Wadi el Obeiyid, moreover, made it possible tohypothesize which areas would have been suitable for human settlement, andthese will be the focus of future surveys.